Juvenile rosacea. - Ybarra, P.; Prados, F.; Crespi, H.; Del Castillo, M.; Anselmi, S.; Ragau, M.; Juarez, M. (European Journal of Pediatric Dermatology, 2018)
In this report, we discuss four cases of rosacea affecting three females and one male aged between nine and fifteen years. Three of these cases showed ocular involvement. In this article, we point out the different clinical course of the four cases and the necessity of an early diagnosis of the ocular complication, during the dermatological observation.